Computer-mediated social support for sexual harassment victims: the case of Sororitas in Indonesia. Issue 4 (12th September 2022) - Simorangkir, Deborah N.; Schumacher, Sharon
Abstract: The objective of this research is to design a computer-mediated social support platform for women in Indonesia who have experienced sexual harassment. In doing so, the following are the research questions that had to be answered: What types of social support are most needed by women victims of sexual harassment? What are the most effective ways to communicate with women victims of sexual harassment? And, what features are most necessary in a CMSS platform for women sexual harassment victims? In-depth interviews with representatives of four organizations that deal with victims of sexual harassment, as well as a survey on 278 Indonesian women were conducted. Data was analyzed through the lenses of the CMSS and Barbee and Cunningham's Support Activation Behavior Coding System (1995) theoretical framework. Findings showed that: Legal and psychological support are the types of support most needed by sexual harassment victims; The most effective ways to communicate with the victims of sexual harassment are by giving assurance of anonymity; allowing them to tell their story uninterruptedly; communicating through an advocate or companion, when needed; getting the family on board; campus visits and campaigns; and, using online tools, and; The most important features in a computer-mediated social support online platform for sexual harassment victims are: Easy accessibility, information, anonymity, means of catharsis, and referral to other organizations. Sororitas was designed based on these findings. However, some tasks still need to be done before launching, including establishing the standard operating procedures, fostering collaborations with partner non-profit organizations, and recruiting website administrators and volunteers. Regular monitoring and evaluation must also be conducted to measure its effectiveness. The healing process for every victim varies greatly, and Sororitas may only be a miniscule part of that process, but the objective is to provide support.